Environmentally Friendly Emergency Lighting System Using Bio Batteries from Pineapple Skin Waste as Energy Source - Neneng Fitrya; Shabri Putra Wirman; Rahmat Dwi Rahayu (Jurnal Ilmu Fisika, 2021)
This study examines the use of bio batteries from pineapple skin paste as an energy source. Bio-battery is a battery with a paste derived from natural materials that are environmentally friendly. The bio-battery is capable of generating electrical power by using a pineapple peel electrolyte paste and copper (Cu) and zinc (Zn) electrodes arranged in series. Parameters measured are voltage, current and duration of the LED (Light Emitting Diode) light. The pasta variations used were pure pasta, pasta with the addition of sodium bicarbonate, pasta with the addition of salt and pasta fermented using LEDs with the total of 6 pieces arranged in parallel and the implementation using pasta with the addition of 0.75 gr salt and 4 LEDs. The research results reveal that the pure paste produces a maximum voltage of 2.410 volts, a maximum current of 0.12 mA with a 14-hour LED light; paste added with sodium bicarbonate produces a maximum voltage of 2,342 volts, a maximum current of 0.21 mA with LED lights on for 12 hours; paste added with salt produces a maximum voltage of 2.432 volts, a maximum current of 0.33 mA with an LED lamp on for 13 hours; and the fermented pasta produced a maximum voltage of 2.542 volts, a maximum current of 0.91 mA. The results showed that bio-battery with pineapple skin paste can produce electrical power that can be used as an energy source for emergency lights.